Brain TDP‐43 pathology in corticobasal degeneration: Topographical correlation with neuronal loss. (23rd January 2022) - Sainouchi, Makoto; Tada, Mari; Fitrah, Yusran Ady; Hara, Norikazu; Tanaka, Kou; Idezuka, Jiro; Aida, Izumi; Nakajima, Takashi; Miyashita, Akinori; Akazawa, Kohei; Ikeuchi, Takeshi; Onodera, Osamu; et al.
Abstract: Aims: Neuronal and glial inclusions comprising transactive response DNA‐binding protein of 43 kDa (TDP‐43) have been identified in the brains of patients with corticobasal degeneration (CBD), and a possible correlation between the presence of these inclusions and clinical phenotypes has been speculated. However, the significance of TDP‐43 pathology in the pathomechanism of CBD has remained unclear. Here, we investigated the topographical relationship between TDP‐43 inclusions and neuronal loss in CBD. Methods: We estimated semi‐quantitatively neuronal loss and TDP‐43 pathology in the form of neuronal cytoplasmic inclusions (NCIs), astrocytic inclusions (AIs), oligodendroglial cytoplasmic inclusions (GCIs), and dystrophic neurites in 22 CNS regions in 10 patients with CBD. Then, the degree of correlation between the severity of neuronal loss and the quantity of each type of TDP‐43 inclusion was assessed. We also investigated tau pathology in a similar manner. Results: TDP‐43 pathology was evident in nine patients. The putamen and globus pallidus were the regions most frequently affected (80%). NCIs were the most prominent form, and their quantity was significantly correlated with the severity of neuronal loss in more than half of the regions examined. The quantities of TDP‐43 NCIs and tau NCIs were correlated in only a few regions. The number of regions where the quantities of TDP‐43 AIs and GCIs were correlated with the severity of neuronal loss was apparently small in comparison with that of NCIs. Conclusions: TDP‐43 alterations in neurons, not closely associated with tau pathology, may be involved in the pathomechanism underlying neuronal loss in CBD. There was a significant topographical correlation between neuronal cytoplasmic aggregation of TDP‐43 and neuronal loss in CBD, suggesting that TDP‐43 protein aberration might be associated with neuronal degeneration in CBD. There was no close correlation between the burden of TDP‐43 and that of tau in neurons. Abstract : There was a significant topographical correlation between neuronal cytoplasmic aggregation of TDP‐43 and neuronal loss in CBD, suggesting that TDP‐43 protein aberration might be associated with neuronal degeneration in CBD. There was no close correlation between the burden of TDP‐43 and that of tau in neurons.